2020
DOI: 10.1017/jns.2020.46
|View full text |Cite
|
Sign up to set email alerts
|

Social support, adherence to Mediterranean diet and physical activity in adults: results from a community-based cross-sectional study

Abstract: There is a growing recognition that social support can potentially exert consistent or opposing effects in influencing health behaviours. The present paper presents a cross-sectional study, including 2,064 adults from Italy, Spain and Greece, who were participants in a multi-centre randomised controlled trial (C4H study), aiming to examine whether social support is correlated with adherence to a healthy Mediterranean diet and physical activity. Social support data were available for 1,572 participants. The maj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Consistent with previous research [ 53 , 54 ], most interviews discussed the importance of community support. Community support encompasses different levels of family, community, and government with manifest and potential support.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with previous research [ 53 , 54 ], most interviews discussed the importance of community support. Community support encompasses different levels of family, community, and government with manifest and potential support.…”
Section: Discussionsupporting
confidence: 76%
“…• Raw and cooked vegetables; fresh fruits Provide ample nutrients, food microbes (see below), dietary fiber, and polyphenols (see below) for the microbiome (see above); Reduces inflammation 44,48,71 ; Improves health outcomes and reduces overall mortality [55][56][57] ; Dietary patterns with ample plant-based foods/fruits/vegetables protect against chronic disease, 58-61,70,138 food allergy, 125 asthma, 7,19,[132][133][134][135][136]139 and allergic rhinitis. 129,[141][142][143] • Whole grains (e.g., wheat, spelt, rye, barley, rice, corn, quinoa, buckwheat); • Potatoes, sweet potatoes, cassava and other starchy roots.…”
Section: Recommended Foods In Age-appropriate Amountsmentioning
confidence: 99%
“…In contrast to the Western dietary pattern, traditional diets consist of seasonal and local foods, prepared at home, and consumed by the family, with culinary methods, transferred from generation to generation. 27 Such diets are sustainable and increase social contact, which also have beneficial effects on health [55][56][57] (Table 3). Each country has its own guidance on healthy eating reflecting country-specific traditional diets, local availability, and recommendations on the intake of macro-and micronutrients to support health.…”
Section: Synergistic Effects Of Nutrients In Dietary Patternsmentioning
confidence: 99%
“…More specifically, eight out of ten participants reported moderate and high adherence to the MD and the mean (SD) MEDAS score of the participants was estimated at 7.31 (2.03). Other studies in Europe and in particular on the Mediterranean region have reported a slight improvement of the diet quality during the pandemic, as indicated by the MEDAS score and other measures of diet quality (Laiou et al , 2020). Women reported higher levels of MD adherence in comparison to men, which is in accordance to other studies conducted in the past (Theodoridis et al , 2018).…”
Section: Discussionmentioning
confidence: 91%